2012
DOI: 10.3390/pathogens1010012
|View full text |Cite
|
Sign up to set email alerts
|

Roles for wbtC, wbtI, and kdtA Genes in Lipopolysaccharide Biosynthesis, Protein Glycosylation, Virulence, and Immunogenicity in Francisella tularensis Strain SCHU S4

Abstract: Using a strategy of gene deletion mutagenesis, we have examined the roles of genes putatively involved in lipopolysaccharide biosynthesis in the virulent facultative intracellular bacterial pathogen, Francisella tularensis subspecies tularensis, strain SCHU S4 in LPS biosynthesis, protein glycosylation, virulence and immunogenicity. One mutant, ΔwbtI, did not elaborate a long chain O-polysaccharide (OPS), was completely avirulent for mice, and failed to induce a protective immune response against challenge wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
0
17
0
1
Order By: Relevance
“…Follow-up studies have confirmed that Schu S4 wbtC and wbtI also play roles in LPS O-antigen synthesis, as both mutants had altered or missing LPS O-antigen, were attenuated in mice infected i.d., and did not protect against low dose Schu S4 aerosol challenge. In addition to its role in LPS O-antigen synthesis, wbtC also appears to play a role in protein glycosylation, as wbtC mutants displayed fewer glycosylated isoforms of both DsbA (see Outer Membrane Proteins Section) and PilA (see Type IV Pili Section), which previously were reported to be glycosylated in F. tularensis (Twine et al, 2012 ).…”
Section: Lipopolysaccharidementioning
confidence: 87%
See 1 more Smart Citation
“…Follow-up studies have confirmed that Schu S4 wbtC and wbtI also play roles in LPS O-antigen synthesis, as both mutants had altered or missing LPS O-antigen, were attenuated in mice infected i.d., and did not protect against low dose Schu S4 aerosol challenge. In addition to its role in LPS O-antigen synthesis, wbtC also appears to play a role in protein glycosylation, as wbtC mutants displayed fewer glycosylated isoforms of both DsbA (see Outer Membrane Proteins Section) and PilA (see Type IV Pili Section), which previously were reported to be glycosylated in F. tularensis (Twine et al, 2012 ).…”
Section: Lipopolysaccharidementioning
confidence: 87%
“…In agreement with other studies demonstrating the importance of LPS in virulence and immunogenicity, Schu S4 kdtA mutants were avirulent in mice via an i.d. infection route but were not protective against Schu S4 aerosol challenge (Twine et al, 2012 ).…”
Section: Lipopolysaccharidementioning
confidence: 99%
“…For the purposes of this study, we focused our attention on transcriptional changes linked to the bacterial envelope, including changes in inner membrane proteins, outer membrane proteins, LPS/capsule synthesis, stress responses, and genes involved in metal uptake/sensing ( Table 2 ). Interestingly, kdtA (required for core oligosaccharide synthesis;[ 63 ]) and wbtA (required for F . tularensis capsule and LPS production; [ 64 ]) were found to be upregulated 1.56- and 1.47-fold ( Table 2 ), respectively, in Δ fmvB , possibly explaining the 50% LPS increase in Δ fmvB ( Fig 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…вместе с тем в литературе мы встретили единственную работу по массспектрометрическому изучению аттенуированных мутантов штамма F. tularensis Schu4, дефектных по различным генам синтеза лпс. как было показано, такие штаммы имели либо идентичный с родительским белковый профиль, либо незначительное снижение высоты основных пиков в зависимости от локализации мутаций [13]. в нашей работе мы провели сравнительный анализ масс-спектров коллекции из 8 изогенных лпс-дефектных (с различными повреждениями структуры лпс) и родительских вирулентных штаммов трех основных подвидов.…”
Section: результаты и обсуждениеunclassified